GAMBARAN PENGETAHUAN IBU HAMIL TENTANG PERSONAL HYGIENE SELAMA KEHAMILAN DI KLINIK ROMAULI - Bernadetta Ambarita; Aprilita Br Sitepu (STIKes Santa Elisabeth Medan, 2020)
Introduction. Pregnancy has an important effect on personal hygiene. Pregnant women are very susceptible to disease. Health and dental hygiene conditions, vaginal hygiene, nail hygiene, and hair hygiene in poor pregnant women can have an impact such as preterm birth, and babies with low birth weight (LBW). The purpose of this research is to find out the level of knowledge of mothers based on parity, age, education, work, and income. Method. This study is descriptive and the population taken as many as 29 pregnant women. Data retrieval is done by NonProbability Sampling technique with the Total Sampling method and carried out by means of direct interviews with respondents assisted with questionnaires.Elisabteh Health Journal : Jurnal Kesehatan, Vol. V No. 01 (Juni,2020) : V-01 E-ISSN 2541-4992Result. Data analysis is performed by univariate analysis. The results of the study of the knowledge of pregnant women on personal hygiene during pregnancy atRomauli Clinic 2019 found that most of the knowledge are 18 people (72%), based on parity, 14 primiparas (56%), based on age, respondents aged 20 -35 years are 23 people (92%), based on senior high school education are 17 people (68%), based on work, respondents were in housewives are 14 people (56%), based on income, there are respondents average in income Rp. 1,500,000 - Rp 2,500,000 for 12 people (48%). Discussion. From the results of the data above the authors conclude that the knowledge of pregnant women at Romauli Clinic has sufficient knowledge about personal hygiene during pregnancy. It is expected that pregnant women can maintain personal hygiene during pregnancy to prevent complications from pregnancy.